2005
DOI: 10.1074/jbc.m502644200
|View full text |Cite
|
Sign up to set email alerts
|

Protein Kinase C Phosphorylation of the Metabotropic Glutamate ReceptormGluR5 on Serine 839 Regulates Ca2+Oscillations

Abstract: The activation of Group 1 metabotropic glutamate receptors, mGluR5 and mGluR1␣, triggers intracellular calcium release; however, mGluR5 activation is unique in that it elicits Ca 2؉ oscillations. A short region of the mGluR5 C terminus is the critical determinant and differs from the analogous region of mGluR1␣ by a single amino acid residue, Thr-840, which is an aspartic acid (Asp-854) in mGluR1␣. Previous studies show that mGluR5-elicited Ca 2؉ oscillations require protein kinase C (PKC)-dependent phosphoryl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
74
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 76 publications
(79 citation statements)
references
References 27 publications
(36 reference statements)
4
74
0
1
Order By: Relevance
“…Early studies have demonstrated that mGluR5 activity elicits high-frequency Ca 2ϩ oscillations that are PKC-dependent. These oscillations are regulated by the direct phosphorylation of the mGluR5 C terminus, with phosphorylation of S839 being required (8,10). We now show that phosphorylation of a second site, S901, is a key mechanism in the regulation of mGluR5-mediated high-frequency Ca 2ϩ oscillations.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Early studies have demonstrated that mGluR5 activity elicits high-frequency Ca 2ϩ oscillations that are PKC-dependent. These oscillations are regulated by the direct phosphorylation of the mGluR5 C terminus, with phosphorylation of S839 being required (8,10). We now show that phosphorylation of a second site, S901, is a key mechanism in the regulation of mGluR5-mediated high-frequency Ca 2ϩ oscillations.…”
Section: Discussionmentioning
confidence: 92%
“…Group I mGluRs are G protein-coupled receptors (GPCRs), which are coupled to phospholipase C, and receptor activation triggers phosphoinositide turnover, release of intracellular Ca 2ϩ , and activation of Protein Kinase C (PKC) (7). Although PKC activity regulates mGluR5-mediated Ca 2ϩ signaling and receptor function (8)(9)(10)(11), there are no studies linking PKC phosphorylation of mGluR5 to receptor surface expression, endocytosis, or intracellular trafficking.…”
mentioning
confidence: 99%
“…Other key mGlu5 receptor interacting proteins, such as PKC, CaM, Siah-1A, and Norbin, also play central roles in integrating synaptic signals to direct mGlu5 receptor signaling and trafficking (Kim et al, 2005;Ko et al, 2012). For example, mGlu1/mGlu5-activated PKC feeds back to phosphorylate and desensitize these receptors (Catania et al, 1991;Aronica et al, 1993;Gereau and Heinemann, 1998;Kammermeier and Ikeda, 2002) and PKC-mediated phosphorylation of serine 839 is involved in the regulation of mGlu5 receptor-mediated Ca 21 oscillations (Kim et al, 2005.…”
Section: General Features Of Mglu5mentioning
confidence: 99%
“…As scaffolding proteins that interact with proline-rich sequences, Homers bring together mGlu1/mGlu5 receptors with IP 3 and ryanodine receptors, Shank, phosphoinositide 3 kinase enhancer-long, and Dynamin III (Bockaert et al, 2010). So-called long Homers have Regulates receptor signaling and internalization Emery et al (2010Emery et al ( , 2012, Rajagopal et al (2010), Kenakin (2011Kenakin ( , 2014, Reiter et al (2012) Regulates receptor signaling and localization Minakami et al (1997), Ishikawa et al (1999), Lee et al (2008), and Ko et al (2012) CaMKIIa Regulates receptor signaling and desensitization Mao et al (2008) and Jin et al (2013) Regulates protein-protein interactions, and mediates receptor signaling and desensitization Catania et al (1991), Aronica et al (1993), Gereau and Heinemann (1998), Kammermeier and Ikeda (2002), Kim et al (2005Kim et al ( , 2008 Decreases receptor surface expression and increases receptor endocytosis Ishikawa et al (1999) and Ko et al (2012) Tamalin Promotes receptor intracellular trafficking and cell surface expression Kitano et al (2002) CAIN, calcineurin inhibitor protein; CAL, cystic fibrosis transmembrane conductance regulator-associated ligand; CaN, calcineurin; NECAB2, neuronal Ca 2+ -binding protein 2; NHERF-2, Na + /H + exchanger regulatory factor 2; PP1g1/2, protein phosphatase 1g1/2; PP2A, protein phosphatase 2A; PP2B, protein phosphatase 2B; Pyk2, prolinerich tyrosine kinase 2. a C-terminal coiled coil domain that allows them to form multiprotein complexes (Hayashi et al, 2006). Short Homers (e.g., Homer 1a) lack the coiled coil domain and thus act as dominant negative proteins (Xiao et al, 2000;Fagni et al, 2002).…”
Section: General Features Of Mglu5mentioning
confidence: 99%
See 1 more Smart Citation